Predictive factors of placental adhesion anomalies: about 24 observations of placenta accreta from CHU Ibn Rochd of CASABLANCA - NKAMBA WA NKAMBA Isaac (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2022)
Placenta accreta is responsible for a significant increase in maternal morbidity and mortality at delivery, due to the risk of massive postpartum haemorrhage leading to maternal death. The identification of key risk factors for placental adhesion defects is an important step in the diagnostic process prior to obstetric ultrasound or abdominal-pelvic Magnetic Resonance Imaging. In this study, we will investigate the main risk factors found in pregnant women with placenta accreta.